2010
DOI: 10.1136/adc.2008.156471
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective review of serological testing of potential human milk donors

Abstract: There is a significant incidence of positive serology among women interested in donating human milk. This implies that there may be significant risk associated with peer-to-peer distribution of human milk from unscreened donors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 21 publications
0
13
0
4
Order By: Relevance
“…The relative risks and benefits of human milk sharing have been the subject of numerous editorials, commentaries and a growing scientific literature (Arnold, 2009; Cohen et al 2010; Landers & Updegrove 2010; Akre et al 2011; Geraghty et al 2011; Gribble & Hausman 2012; Nelson 2012; Brent 2013; Geraghty et al 2013; Keim et al 2013, 2015; Landers & Hartmann 2013; Updegrove 2013a,b; Gribble 2014c; Keim et al . 2014a,b; Martino & Spatz 2014; Carter et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The relative risks and benefits of human milk sharing have been the subject of numerous editorials, commentaries and a growing scientific literature (Arnold, 2009; Cohen et al 2010; Landers & Updegrove 2010; Akre et al 2011; Geraghty et al 2011; Gribble & Hausman 2012; Nelson 2012; Brent 2013; Geraghty et al 2013; Keim et al 2013, 2015; Landers & Hartmann 2013; Updegrove 2013a,b; Gribble 2014c; Keim et al . 2014a,b; Martino & Spatz 2014; Carter et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…However, they have also been reported in other areas, such as European countries (68), the United States (11,51,73), the Caribbean area (17,57), Central and South America (Brazil, Argentina) (6,35,44,50,61), and more recently the Middle East (74). Most of the studies concern blood donors (10,11,16,63) or epidemiological work in the general population (43) but also organ donors for transplantation (22,36), lactariums (19,58,70), and neurological patients (1,73). Indeed, the finding of an indeterminate WB HTLV serology raises questions not easy to be resolved by the medical doctors in charge of the persons with such an indeterminate pattern.…”
Section: Discussionmentioning
confidence: 99%
“…(14)(15) For example, of 1091 potential donating mothers at the San Jose Bank in California, 3.3% were positive for an infectious disease, including syphilis, hepatitis B, human T-lymphotropic virus, and human immunodeficiency virus. (14) Kiem et al (15) found that milk randomly purchased on the Internet had significant bacterial contamination with organisms potentially dangerous in the NICU setting.…”
Section: What Is Pdhm?mentioning
confidence: 98%